Species diversity and catch per unit effort of fish in a perturbed tropical lake, Ibadan, Nigeria - Adedolapo A. Ayoade; Omotolani M. Owolabi; Omolayo T. Patience; Oluwatobi R. Adeduntan; Praise Kujooro (Academia Biology)
Eleyele Lake serves the purpose of domestic water supply, transportation, and fisheries; therefore, it is a source of food and livelihood to the artisanal fishers in Ibadan. However, various reports indicated the perturbed state of the lake, which can have adverse effects on the ecosystem services including fisheries. Therefore, this study investigated the catch per unit effort (CPUE) of fish in the Eleyele Lake and some physicochemical parameters in order to establish the status of the fisheries of the lake. Water samples were collected from the lake and analyzed. The fish catches, effective fishing effort (EFF), and CPUE of the lake were determined. The dissolved oxygen and transparency levels were not within the recommended permissible limits. Fish encountered in the lake during the study period belong to nine families and fifteen species. Cichlidae, Polypteridae, and Clariidae were the most frequently encountered families. Shannon-Weiner (2.23), Margalef (2.14) diversity indices, and Evenness (0.87) were highest during the sampling period in 2019. The EFF was 0.37 kW day−1. The mean CPUE increased from 9.55 ± 1.67 kg·kW day−1 in 2019 to 38.07 ± 30.89 kg·kW day−1 in 2021 and declined to 6.44 ± 3.02 kg·kW day−1 in 2023. The forage /carnivore ratio was 0.70 in 2019, 0.35 in 2021, and 54 in 2023 by number indicating an imbalance in the fish population. This study implies that effective management and sustainable exploitation of the fisheries in the Eleyele Lake require improvement of water quality and enforcement of a closed season.